1987
DOI: 10.1104/pp.84.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Medicarpin Biosynthesis in Ladino Clover Callus by p-Chloromercuribenzoic Acid Is Reversed by Dithiothreitol

Abstract: Treatment of Ladino clover (Trifolium repens L.) callus with 1 millimolar p-chloromercuribenzoic acid (PCMBA) stimulated the biosynthesis of the phytoalexin medicarpin. Increased medicarpin concentration was detected at 6 hours, and maximum level was achieved by 36 hours. Dithiothreitol (DTT), added to callus at 2, 6, 10, and 18 hours following addition of PCMBA, partially counteracted the effect of PCMBA in the cells. The greatest effect on reversal of medicarpin accumulation was found at the earlier times fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Moreover, certain sulfhydryl reagents stimulate the production of phytoalexins and the activation of other defense responses associated with the expression of disease resistance (11,24). Taken together these observations suggest that glutathione may play a role in mediating the response of plant cells to biological as well as physical stresses.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, certain sulfhydryl reagents stimulate the production of phytoalexins and the activation of other defense responses associated with the expression of disease resistance (11,24). Taken together these observations suggest that glutathione may play a role in mediating the response of plant cells to biological as well as physical stresses.…”
mentioning
confidence: 66%
“…Moreover, certain sulfhydryl reagents stimulate the production of phytoalexins and the activation of other defense responses associated with the expression of disease resistance (11,24). Taken …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3A) or that SOD activity within the bacteria and plant cells was sufficient to convert any O-to H202. Because O-in the plant cells may react with H202 produced during the oxidative In white clover callus, an induction period of up to 6 h was necessary before medicarpin levels increased (14,16). Increased rate of K+/H+ exchange, an indicator of HR, is first detected in an incompatible interaction 2 to 6 h following addition of P. syringae pv syringae to tobacco suspension cells (7).…”
Section: Discussionmentioning
confidence: 99%
“…and H202 have been observed in plant cells soon after elicitor treatments (Aposto1 et al, 1989;Anderson et al, 1991;Arnott and Murphy, 1991;Vera-Estrella et al, 1992) or upon * Corresponding author; fax 33-42-25-46-56. challenge with pathogens (Chai and Doke, 1987;Adam et al, 1989;Baker et al, 1991;Glazener et al, 1991;Devlin and Gustine, 1992). In addition, it has been shown that severa1 cellular redox state-modifying compounds, such as sulfhydryl reagents, are able to elicit the accumulation of the isoflavonoid phytoalexins in clover callus (Gustine, 1981(Gustine, , 1987 and in soybean (Glycine max) hypocotyls (Stossel, 1984). It is difficult to assume that there is direct biological relevance to such sulfhydryl modified groups.…”
mentioning
confidence: 99%